Effectiveness and performance of e-government in Saudi Arabia - Taha Alshaikhli, Haifa; Alzuabi, Imad Fakhri (IIUM Press, International Islamic University Malaysia, 2017)
The purposes of this book are to investigate the effectiveness of e-government implementation in Saudi Arabia, explore the underlying factors for the efficient performance of e-government portals, address the gaps and problems that have emerged in e-government portals, examine the impact of the problems found in e-government plan and the needs of its citizens, give the recommendation on the improvement of the performance of e-government portals in order to serve Saudi citizens and its users in the most effective manner.